Facile Polymer Functionalization of Hydrothermal‐Carbonization‐Derived Carbons - Urakami, H.; Yilmaz, A.; Osiceanu, P.; Yagci, Y.; Vilela, F.; Titirici, M. (Wiley, 2013)
AbstractA simple and efficient polymer grafting onto hydrothermal carbonization (HTC)‐derived materials is described. The method pertains to the Diels–Alder cycloaddition reaction of furan moieties present on the surface of a HTC material with the maleimide groups stemming from a maleimide protected poly(ethylene glycol) (Me‐PEG‐MI) by a retro Diels‐Alder reaction. The precursor polymer, HTC material, and final product are characterized. Successful grafting is confirmed by elemental analysis, X‐ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and dispersion studies.magnified image
Keywords: Maleimides; Hot Temperature; Cycloaddition Reaction; Photoelectron Spectroscopy; Spectroscopy, Fourier Transform Infrared; Furans; Carbon; Polyethylene Glycols